DESIGNING A WEB-BASED ELEMENTARY SCHOOL ATTENDANCE SYSTEM USING THE LARAVEL FRAMEWORK - Abdul Rezha Efrat Najaf; Jeremy David Alexander; Khoirul Tarmidzi; Fajar Kurnia (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2023)
The era of globalization has produced transformational innovations and has the potential to drive innovation, productivity, and digital transformation. Digital transformation is an important issue and is a habit that must be applied in all industrial sectors. The implementation of digital transformation will provide competencies and skills that can adapt to various changes, especially those related to digital transformation. One sector that must immediately carry out digital transformation is the education sector. For this reason, the education sector absolutely requires human resource development as a way to improve abilities and skills. Based on literature studies, it has been obtained that the steps of the Waterfall method. The results obtained from the research are software development using the Waterfall method and the Laravel framework according to predetermined stages. At this stage, several components that are needed in making the system and restrictions in making the system will be explained, including the following: Software Requirements, Activity Diagram, and System Results. This attendance website is useful for teachers to be able to take attendance of their students online, this attendance website can recap attendance data automatically in PDF form which of course can facilitate the work of teachers, and with this attendance website, students and parents can monitor attendance data managed by teachers.